Establishing the adequacy of recorded acoustic surveys of forest bird assemblages - Michael J. M. Franklin; Richard E. Major; Michael Bedward; Ross A. Bradstock (Avian Conservation and Ecology, 2020)
The use of programmable acoustic recorders to survey forest birds is increasing owing to a range of advantages over surveys conducted by human observers. Users of these devices require a methodological framework for designing and testing a proposed survey protocol in context, to be assured that it has the capacity to efficiently meet the requirements of their study. We aimed to demonstrate how a potential acoustic survey protocol may be effectively tested by comparison with either (1) an observer-based method using species detection probabilities, or (2) the survey completeness levels among a set of other candidate acoustic protocols. Surveys using acoustic recordings (manually processed) and standardized area searches were conducted over the same period in dry sclerophyll forests of southeastern Australia. A multispecies occupancy modeling framework was used to obtain estimates of the probability of detecting individual species for both standardized searches and an acoustic protocol representing similar temporal sampling effort. Detection probabilities for 73% of species recorded using these methods were greater with the acoustic protocol than standardized searches, which established its adequacy for particular research questions. The survey methods resulted in a similar pattern of detection probabilities for foraging stratum guilds, although members of the canopy/subcanopy guild were less likely to be detected using both methods. Survey completeness (species detected/total species) was adopted as an alternative framework for acoustic protocol evaluation. The complete acoustic data set was (1) used with the incidence-based coverage estimator (ICE) to obtain the total number of species, and (2) subsampled to produce a candidate set of potentially useful survey protocols. Completeness levels ranged from 62% to 73% in the set, which provided options for subsequent protocol selection. Other ecologists may adopt one of the frameworks to establish the adequacy of their own acoustic survey protocol to suit their research question and available resources.